The effect of water vapor on high temperature oxidation of Fe-Cr alloys at 1073K - Ani, Mohd Hanafi; Kodama, Toshiya; Ueda, Mitsutoshi; Kawamura, Kenichi; Maruyama, Toshio (Japan Institute of Metals, 2009)
The effect of water vapor on high temperature oxidation was studied based on Wagner’s theory of binary alloy oxidation. The oxidation of Fe-Cr alloys was carried out at 1073K in dry and humid conditions. The oxidation was conducted in a closed apparatus at 1073K and the oxygen partial pressure of 1:1 1014 Pa, which was fixed by a Fe/FeO buffer. To prepare the humid condition, Ar-5% H2 gas mixture of 3 104 Pa was filled in the apparatus, which provided the water vapor pressure of 3:3 102 Pa. The transition of internal and external oxidation was observed in Fe-8Cr in the dry condition and in Fe-12Cr in the humid condition. Interdiffusion experiment of Fe/Fe-16Cr diffusion couples in dry and humid environments showed that the diffusion coefficient of Cr was not influenced by dissolved hydrogen. The oxygen permeability in -Fe was determined by means of internal oxidation of Fe-5Cr alloy at 1073K and the oxygen partial pressure of 1:1 1014 Pa in a dry and two humid conditions with water vapor of 1:1 102 Pa and 3:3 102 Pa. The oxygen permeability in humid condition increases by a factor of 1.4. Dissolved hydrogen increases the oxygen permeability, thus increases the minimum concentration of Cr to form external scales in humid conditions. The presence of dissolved hydrogen changes the oxide shape from discrete spherical particle to spikelike precipitates, which enhances the oxygen transport along the metal/oxide precipitates interface.